Prognostic value of circulating neuron-specific enolase combined with erythrocyte and platelet distribution indices in patients with severe traumatic brain injury: Circulating biomarkers for prognosis of severe TBI - Li, Tengyu; Ma, Dingjun; Zhang, Guozhen; Wang, Chao; Xu, Bin; Zhu, Weidong (Journal of Medical Biochemistry, 2026)
Background: Severe traumatic brain injury (STBI) is associated with high mortality and long-term neurological disability. Early identification of reliable circulating biomarkers may improve prognostic stratification and clinical management. Hematological distribution indices, including red cell distribution width (RDW) and platelet distribution width (PDW), together with neuron-specific enolase (NSE), reflect systemic inflammation, platelet activation, and neuronal injury following traumatic brain damage. However, their combined prognostic value in STBI remains incompletely understood. Methods: A retrospective study was conducted including 96 patients with STBI admitted between March 2020 and March 2023. Peripheral blood levels of RDW, PDW, and serum NSE were measured at admission using automated hematology analysis and enzyme-linked immunosorbent assay. Clinical severity was additionally assessed using the reverse shock index multiplied by Glasgow Coma Scale score (rSIG). According to the Glasgow Outcome Scale (GOS) evaluated 3 months after injury, patients were classified into a good prognosis group (n=46) and a poor prognosis group (n=50). Logistic regression analysis was performed to identify independent prognostic factors, and receiver operating characteristic (ROC) curves were used to evaluate predictive performance. Results: Patients with poor prognosis demonstrated significantly higher levels of RDW, PDW, and NSE and lower rSIG values compared with those with favorable outcomes (P<0.05). Multivariate logistic regression analysis identified elevated RDW, PDW, and NSE levels and decreased rSIG as independent predictors of unfavorable prognosis in STBI patients. ROC analysis revealed moderate predictive performance for RDW (AUC=0.737), PDW (AUC=0.749), NSE (AUC=0.736), and rSIG (AUC=0.752). The combined biomarker model demonstrated improved prognostic accuracy (AUC=0.793). Conclusions: Circulating NSE together with hematological distribution indices RDW and PDW are significantly associated with clinical outcomes in patients with severe traumatic brain injury. The combined assessment of neuronal injury biomarkers and hematologic parameters may provide a practical laboratory-based approach for early prognostic evaluation in STBI.